Numerical Modeling of Interactions between Solitary Waves and Floating Breakwaters - Malazi, M. Tabatabaei; Dalkilic, A. S.; Wongwises, S. (ISFAHAN UNIV TECHNOLOGY, 2022)
In the current numerical work, a 2D wave tank has been planned to explain the shared impacts among three different solitary waves and three different floating breakwaters by applying Reynolds-Averaged Navier-Stokes models and the volume of fluid method. Three dissimilar floating breakwaters (i.e., square breakwater, circular breakwater, and modified breakwater) were chosen. A total of eighteen cases were investigated, including three different floating breakwaters, a solitary wave (SW) with three different wave heights, and two different densities of floating breakwaters. We achieved the production of a solitary wave by moving a wave paddle (WP) and the motion of floating breakwater in two various directions by applying two different codes as user -defined functions. The dynamic mesh technique has been employed for re-forming mesh during the motion of the wave paddle and the floating breakwater. The numerical calculations have been confirmed by some numerical, analytical, and experimental case studies. First, the generation of a SW using the WP movement and the free motion of a heaving round cylinder on the free surface of motionless water were modeled and validated. Additionally, the effects of various parameters, including floating breakwater shape, floating breakwater density, and solitary wave height, on the hydrodynamic performances of the floating breakwater, the floating breakwater's motions, and the free-surface elevation were considered under various conditions.
Keywords: Floating breakwater; Wave-structure interaction; Solitary wave; CFD; VOF; HYDRODYNAMIC PERFORMANCE; SIMULATION; PROPAGATION; Thermodynamics; Mechanics